Defining high‐risk elective contralateral neck radiation volumes for oropharynx cancer. Issue 2 (11th November 2021) - Witek, Matthew E.; Woody, Neil M.; Musunuru, Hima B.; Hill, Patrick M.; Yadav, Poonam; Burr, Adam R.; Ko, Huaising C.; Ross, Richard B.; Kimple, Randall J.; Harari, Paul M.
Abstract: Background: To define the location of the initial contralateral lymph node (LN) metastasis in patients with oropharynx cancer. Methods: The location of the LN centroids from patients with oropharynx cancer and a single radiographically positive contralateral LN was defined. A clinical target volume (CTV) inclusive of all LN centroids was created, and its impact on dose to organs at risk was assessed. Results: We identified 55 patients of which 49/55 had a single contralateral LN in level IIA, 4/55 in level III, 1/55 in level IIB, and 1/55 in the retropharynx. Mean radiation dose to the contralateral parotid gland was 15.1 and 21.0 Gy, ( p <0.001) using the modeled high‐risk elective CTV and a consensus CTV, respectively. Conclusions: We present a systematic approach for identifying the contralateral nodal regions at highest risk of harboring subclinical disease in patients with oropharynx cancer that warrants prospective clinical study.